THE EFFECTIVENESS OF LOCAL REGULATION MAKING IN THE DPRD OF SPECIAL REGION OF YOGYAKARTA - Jufri Irawan (FH 15 UMY 152, 2015)
*152 Since 2013 until 2015, the target of Raperda is diminishing in every year. The data reveal that the DPRD and the local government never achieve the target of local regulation making drafted in the Prolegda. The main problem in this matter is the effectiveness of local regulation making in the DPRD of Special Region of Yogyakarta, where the role of local regulation is very important in the implementation of local autonomy. This article is a scientific work that aims to understand the mechanism of local regulation making, to analyze the effectiveness of local regulation making in the DPRD of Special Region of Yogyakarta and to understand some obstacles face by the DPRD and the local government in the local regulation making in Special Region of Yogyakarta. The method used in this research is normative research and empirical research. The result of this research is that the implementation of local regulation making in Special Region of Yogyakarta is not effective and also there are so many obstacles in the implementation of it, as like as lack of budget, lack of the DPRD member, lack of time, etc. Therefore, the local government should be better in takes into account the ability whether material and formal in forming of local regulations before input into Prolegda and very necessary the public participation in its implementation. In the local regulation making, it will be effective if the government and the DPRD plan to produce smaller numbers of local regulation, but the government and the DPRD can achieve the target